Ideological adaptation as a strategy of dominance in alliances between competing parties in the Valencian Community - Marcelo Guillén García (Revista d'Estudis Autonòmics i Federals)
This article adapts theories of partisan competition to the dynamics of alliances between political parties, considering ideology as a contingent element that parties can use to achieve their objectives. Based on these theories, it is suggested that, in alliances between competing parties, the larger party can adapt its ideology to that of the smaller party in an attempt to dominate and take over its hunting ground. To this end, three examples of such alliances in the Valencian Community are analysed: Unió Valenciana and Partido Popular de la Comunidad Valenciana, Unitat del Poble Valencià and Partit Valencià Nacionalista, and Bloc Nacionalista Valencià and Iniciativa del Poble Valencià (Compromís). The analysis confirms the initial expectation, although different factors are identified that influence it. First, the degree of inequality between allies determines the form of dominance of the larger party and the evolution of the alliance. Second, the existence of a complex territorial dimension in the Valencian Community favours the ideological adaptation of the allies. Furthermore, it follows that even if a new identity is generated in the alliance, as in the case of Compromís, the larger party can adapt to it and seek to neutralise its ally.